FAIR: The Future European Facility for Antiproton And Ion Research - Münzenberg, G. (HNPS Advances in Nuclear Physics, 2020)
FAIR, the new international Facility for Antiproton and Ion Research at GSI, will cover a broad spectrum of hadronic, nuclear, and atomic physics research and appli- cation. A system of synchrotrons will provide intense proton and heavy ion beams of intermediate energy with the option to produce secondary beams of radioactive nuclei and antiprotons. NUSTAR, NUclear STructure, Astrophysics and Reactions, will play a premier role within the FAIR research program. Nuclei at the limits of binding will become accessible and new probes for reaction studies with unstable nuclei become available.